Posisi Guru Madrasah di Tengah Kompleksitas Problematika Pendidikan Nasional - Nuryamujiatun, Nuryamujiatun (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2021)
Madrasa teachers demand an important role in people's lives, as well as a higher level of religious knowledge compared to professional teachers in general. Labeling attached as mudaris, murabbi, and mu'allim. This study aims to determine the position of madrasa teachers in the midst of the complexity of the problems of national education. The approach used is literature review where the review processes, thoroughly understand a particular topic. While the method used is content analysis, which looks for data sources from journals, books, and scientific articles. The results of the research are that the position of madrasa teachers in the midst of the complexity of the problems of national education as an effort to optimize learning more significantly, madrasa teachers are very influential in national education today who have roles, duties, and responsibilities as well as educators, as mentors and provide evaluations. Where madrasah teachers have two problems, namely internal and external.